Kompentensi Sel (Social And Emosional Learning) Untuk Anak Usia 5-6 Tahun - Widia Asri Kurnia; Heri Yusuf Muslihin; Sumardi Sumardi (JURNAL PAUD AGAPEDIA, 2023)
This research is motivated by the current conditions where activity restrictions greatly affect the social emotional development of children. Based on the facts, early childhood should be able to get optimal guidance and teaching in their surrounding environment. Developing social emotional skills from an early age can be a benchmark for children's success in the future. In this regard, it is important for parents and educators to maintain the mental health and welfare of children so that children can progress according to their developmental stages. One of the reference films related to emotion is film animation Inside Out. The purpose of this study is to determine the components of SEL (Social and Emotional Learning) by analyzing the animated film Inside Out. The approach used is a qualitative approach with content analysis methods (content analysis). Data collection techniques in the form of literature study, observation and documentation. The results of this study indicate that some of the indicators in the SEL (Social and Emotional Learning) component are in accordance with the Standar Tingkat Pencapaian Perkembangan Anak (STPPA) in the scope of social emotional development for children 5-6 years old. Inside Out is also considered worthy of being used as a learning medium through cinematherapy to develop early childhood social-emotional skills. Penelitian ini dilatar belakangi oleh kondisi saat ini dimana pembatasan aktivitas sangat mempengaruhi pada perkembangan sosial emosional anak. Berdasarkan fakta yang ada, anak usia dini sewajarnya dapat memperoleh bimbingan dan pengajaran yang optimal di lingkungan sekitarnya. Mengembangkan keterampilan sosial emosional sejak dini dapat menjadi tolak ukur dalam keberhasilan anak di masa yang akan datang. Berkaitan dengan hal tersebut, penting bagi orang tua maupun pendidik untuk menjaga kesehatan mental dan kesejahteraan anak agar anak dapat berprogres sesuai dengan tahap perkembangannya. Salah satu film rujukan yang terkait dengan emosi yaitu film animasi Inside Out. Tujuan dari penelitian ini yaitu untuk mengetahui komponen SEL (Social and Emotional Learning) dengan menganalisis film animasi Inside Out. Pendekatan yang digunakan yaitu pendekatan kualitatif dengan metode analisis konten (analysis content). Teknik pengumpulan data berupa studi pustaka, observasi dan dokumentasi. Hasil dari penelitian ini menunjukkan bahwa beerapa indikator dalam komponen SEL (Social and Emotional Learning) sesuai dengan Standar Tingkat Pencapaian Perkembangan Anak (STPPA) dalam lingkup perkembangan sosial emosional untuk anak 5-6 tahun. Film animasi Inside Out juga dianggap layak untuk dijadikan media pembelajaran melalui cinematheraphy guna mengembangkan keterampilan sosial emosional Anak Usia Dini.